Implementation of Differentiated Mathematics Learning in Quadratic Functions at Senior High Schools - Nanang Inwanto; Sutama; Ahmad Muhibin (Didaktika: Jurnal Kependidikan, 2025)
This article discusses differentiated learning in mathematics at SMAN 4 Surakarta, focusing on how this approach is implemented in the quadratic function material. The research uses a qualitative methodology with a single-anchored approach, employing triangulation of data sources and methods to ensure data validity. Data collection was done through document analysis, in-depth interviews, and observations. The findings reveal that mathematics teachers initially used differentiated learning strategies to develop and implement math modules. In the learning process, differentiation is applied through varying content, processes, and products in the quadratic function material. Teachers also use assessments based on cognitive, affective, and psychomotor guidelines for evaluation. The study concludes that differentiated learning enhances students' critical and creative thinking skills in mathematics, although challenges such as limited facilities, infrastructure, and insufficient learning time are noted. This research provides implications for improving instructional strategies and educational practices to foster a more inclusive and effective learning environment.